Urease Inhibitor and Irrigation Management to Mitigate Ammonia Volatilization from Urea in No-Till Corn - Viero,Fernando (2017)
ABSTRACT High nitrogen (N) losses by ammonia (NH3) volatilization from urea can compromise nitrogen fertilization efficiency and corn yield. The purpose of this study was to assess the effects of irrigation management and the addition of the urease inhibitor N-(n-butyl)thiophosphoric triamide (NBPT) on NH3-N losses from urea and on corn yield. To this end, two experiments were carried out in the 2011/12 crop season on a sandy clay loam Acrisol in the Central Basin region of Rio Grande do Sul, southern Brazil. Experiment I consisted of two different N sources (urea and urea plus the inhibitor) at a rate of 200 kg ha-1 N and two corn sowing times [viz., an early time (Sept. 3, 2011) and an intermediate time (Oct. 3, 2011)]. Experiment II considered a combination of three irrigation management systems (viz., without irrigation on the fertilization day and on the next 7 days; 20 mm of water immediately before N fertilization; and 20 mm water after N fertilization) and two N sources (urea and urea plus the inhibitor) at 150 kg ha-1 N. A control treatment without topdressed N fertilization was also performed in parallel with the two experiments. The NH3-N losses from common urea increased with increasing soil moisture in Experiment I (25 % applied N), and with irrigation before N fertilization in Experiment II (27 % applied N). The inhibitor reduced NH3-N losses from urea by 46 to 80 %. Also, irrigation after fertilization reduced ammonia volatilization by 83 % on average, with little effect from the inhibitor. The effects of the inhibitor and post-fertilization irrigation on the mitigation of NH3 losses by volatilization from urea were not additive; in addition, they led to no increase in corn yield.